Genome-wide analysis of fitness-factors in uropathogenic Escherichia coli during growth in laboratory media and during urinary tract infections. Issue 12 (20th December 2021) - García, Vanesa; Grønnemose, Rasmus B.; Torres-Puig, Sergi; Kudirkiene, Egle; Piantelli, Mateo; Ahmed, Shahana; Andersen, Thomas E.; Møller-Jensen, Jakob; Olsen, John E.; Herrero-Fresno, Ana
Abstract : Uropathogenic Escherichia coli (UPEC) UTI89 is a well-characterized strain, which has mainly been used to study UPEC virulence during urinary tract infection (UTI). However, little is known on UTI89 key fitness-factors during growth in lab media and during UTI. Here, we used a transposon-insertion-sequencing approach (TraDIS) to reveal the UTI89 essential-genes for in vitro growth and fitness-gene-sets for growth in Luria broth (LB) and EZ-MOPS medium without glucose, as well as for human bacteriuria and mouse cystitis. A total of 293 essential genes for growth were identified and the set of fitness-genes was shown to differ depending on the growth media. A modified, previously validated UTI murine model, with administration of glucose prior to infection was applied. Selected fitness-genes for growth in urine and mouse-bladder colonization were validated using deletion-mutants. Novel fitness-genes, such as tusA, corA and rfaG; involved in sulphur-acquisition, magnesium-uptake, and LPS-biosynthesis, were proved to be important during UTI. Moreover, rfaG was confirmed as relevant in both niches, and therefore it may represent a target for novel UTI-treatment/prevention strategies.